Impact of wild pigs in agriculture and their management - Rai, Sajana (Journal of Agriculture and Natural Resources, 2023)
Wild pigs cause substantial damage to the agriculture crops and leads to the economic loss of rural farmers. They harm the environment by shifting plant composition and decreasing its productivity. Wild pigs destroy habitat, predation and competes for resources with rare, threatened and endangered species in ecosystem. Their damage in fields can be accessed by regular monitoring which can be achieve by the use of drones. The management approaches to control wild pig encroachment in farm lands are baiting, hunting, fencing and catching with the use of dogs. Among them shooting or hunting is more common in practice. In addition, they transmit the various diseases like classical swine fever and Brucella spp. to livestock. This review summarizes the importance of wild pigs as genetic resources, factors affecting human-wild pig conflict, crop raiding and economic loss and various management approaches. This study suggests the controlling of wild pigs in farm lands which leads to the increase in agricultural production.